(untitled) (WAKTU: Jurnal Teknik UNIPA, 2024)
Magersari Subdistrict is one of the subdistricts located in Mojokerto City which has a risk area for domestic wastewater, household waste and environmental drainage. The method used in this study is descriptive qualitative and quantitative with data collection techniques used in this study, namely observation and questionnaire results in residential areas. The purpose of this study was to determine the condition and risk level of the current settlement sanitation in Magersari District, Mojokerto City. The results of the analysis obtained through the questionnaire were then calculated using the Likert scale index. It can be seen that the Balongsari Village has sufficient criteria with an interval of 60.66% - 65.16%, while the Magersari Village has sufficient criteria with an interval of 60.31% - 64.8% , and Kedundung Village has sufficient criteria with an interval of 61.31% - 68.68%. Based on the results of the analysis obtained by Magersari District, until now it still has sufficient sanitation facilities and infrastructure to meet the needs of its people, but it is necessary to improve the quality of waste facilities that have been damaged.